Incidental Primary Intrathoracic Goiter: Dual-Isotope Scintigraphy and Early-MIBI SPECT/CT - E. Zamora; S. Ghandili; M. A. Zamora; K. J. Chun (World Journal of Nuclear Medicine)
Primary intrathoracic goiter is an uncommon congenital entity resulting from over decent ectopic thyroid tissue. As compared with secondary intrathoracic goiter, primary entities are discrete from orthotopic thyroid tissue and may lead to potentially serious complications such as malignancy and shortness of breath. Intrathoracic goiters have been described as showing mild or absent uptake of 99mTc-pertechnetate on planar scintigraphy. We present an incidental primary intrathoracic goiter found in a patient undergoing evaluation with multimodal scintigraphy and early 99mTc-sestamibi single-photon emission computed tomography/computed tomography (SPECT/CT) for localization of parathyroid adenomas. The mass was inconspicuous on TcO4- scintigraphy but methoxyisobutylisonitrile-avid on early planar and SPECT/CT.